O descoroamento da Princesa do Sertão : de "chão" a território, o "vazio" no processo de valorização do espaço - Freitas, Nacelice Barbosa (2014)
To study the process of territorial formation in the state of Bahia, we catagorised Feira de Santa in scaled sections, aiming to unveil euphemism and practices that create the powers supported by political and economic institutions on this geographical scale. The study focuses on the Sertão/territory as the locus of implementation of the territorial capital, a space which is understood as a dialectical relationship in its multiple scaled dimensions. The difference between litoral and sertão (coastal & dry land) explained under the Marxist orientation, falls within the social and territorial division of labour, where the social and political are subjected to the scrutiny of the capital in its multiple determinations. The reality is contradictory in its making and remaking the geography of the sertão (dry land) and signifies the concreteness of this movement. The starting point-is that Feira de Santana-is the scale of analysis, a place that serves as the foundation for the pursuit of know ledge about the territorial formation of the sertão. The construction/creation of the Bahian sertão establishes a challenge to consider the economic and political importance of the geographical location of Feira de Santana, as Princess and Portal of the Sertão. The research process has made it possible to understand the profound changes in its urban space and the historical context helping to establish the city as Princess of Sertão. The investigation led to the territorial analysis treated as the sertanejo- litorâneo relationship, which is the formation of the Brazilian nation. In conclusion, it is the Sertão that creates a Brazilian nationality, therefore this is a space that is instructed to carry a nomenclature full of stereotypes and multiple meanings. Feira de Santana is included in this place considered by many scholars as a space of no precise location, undefined, the fragile borders. There is a primitive accumulation and store of value in the territory. This condition causes a transformation into ground territory, where the idea of emptiness throughout space-time, is an essential context to the process of creating value for the capital. The Sertão, in the sertanejo area, assumes different meanings in constituting the streams of the capital.